1988
DOI: 10.1016/0550-3213(88)90074-0
|View full text |Cite
|
Sign up to set email alerts
|

The renormalization flow in the adjoint SU(2) lattice Higgs model

Abstract: Applying the Monte Carlo renormalization group method we investigate the flow of coupling constants for the 84 and 164 SU(2) lattice Higgs model with triplet Higgs fields. The couplings of the renormalized actions are determined using Schwinger-Dyson equations. From the flow we find new evidence for the existence of a tricritical point at finite values of the inverse gauge coupling fl but no indication for a discontinuity fixed point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…This is discussed in detail in appendix A. Especially, we found that with better thermalization properties the results on the phase diagram from exploratory investigations [19][20][21][22][23] changed, and especially the phase transition shifted to larger values of κ for larger volumes. The reason for this is likely the presence of the massless gauge-invariant vector particle, and thus slow decorrelation and large finite-volume effects.…”
Section: Phase Diagram and Simulation Pointsmentioning
confidence: 76%
See 1 more Smart Citation
“…This is discussed in detail in appendix A. Especially, we found that with better thermalization properties the results on the phase diagram from exploratory investigations [19][20][21][22][23] changed, and especially the phase transition shifted to larger values of κ for larger volumes. The reason for this is likely the presence of the massless gauge-invariant vector particle, and thus slow decorrelation and large finite-volume effects.…”
Section: Phase Diagram and Simulation Pointsmentioning
confidence: 76%
“…Our lattice implementation will be given in Section 3, with some details relegated to appendix A. In particular, we found that early investigations of the phase diagram of this theory [19][20][21][22][23] likely underestimated systematic effects due to the finite volume and length of Monte Carlo trajectories, similar to what has happened in the fundamental case [24]. These effects are quite severe, and thus also in our case we cannot yet offer a full systematic analysis in terms of discretization artifacts, though volume effects will be investigated in great detail.…”
Section: Introductionmentioning
confidence: 99%
“…These two transitions are connected by a phase transition line that separates the Higgs and confining phases. There is evidence for a tricritical point at finite (κ, β) at which the transition changes from first to second order [31], but it is not known if the tricritical line extends to λ = 0.…”
Section: Discussionmentioning
confidence: 99%
“…These results will be reviewed in the following. Almost all of these investigations have been performed in four dimensions for the standard model case [46, 144, 158-160, 162, 186-191, 194-200, 203, 204, 206], and only very few addressed other theories [180,184,185,192,193,201,202,205,[207][208][209][210][211][212].…”
Section: The Phase Diagram From the Latticementioning
confidence: 99%